The Effect of Skill-Rehabilitation Exercises Using an Assistive Device on Modifying Forward Head Fall and Compound Skill Performance in Fencing Players - Awda, Asst. L. Ali Hamid; student, L. Dr. Karrar is a Muslim; Amir, Asst. L. Mustafa Alaa Abdul (Sulaimani Journal for Humanities, 2026)
The research aims to record a skill-rehabilitation exercise using a tool to help determine the head fall and to identify skill-rehabilitation impact exercises using an aid in the skill performance level of fencers. It was used experimentally by an experimental group of pre- and post-eye embroidery. The research community was represented by third-year physical fitness students in the College of Education and Sports Sciences - University of Babylon, where their number was (54) students. The main research was represented by (6) labs to test it to the end. A researcher contributed to a pilot experiment on (3) students from the same main research. She also used technology, testing, measurement and observation. The research highlighted the Arab and foreign references. The research showed that practicing skill-rehabilitation with an aid plays an effective and positive role in actually modifying the head fall forward at the skill performance level of ambitious fencers, with excellence as it has an experimental group in the test. Among the least research criteria for the use of skill-rehabilitation is the use of aids in modifying incorrect behaviors to deform the body, the head, neck and back fall, in addition to conducting other studies on deformities. Students usually have pupils
Keywords: Skills exercises; assistive devices; forward head fall; complex attack